2017
DOI: 10.2337/cd16-0037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of A1C to Oral Glucose Tolerance Test for the Diagnosis of Prediabetes in Overweight and Obese Youth

Abstract: IN BRIEF This study reports performance of A1C against the oral glucose tolerance test (OGTT) in predicting prediabetes among overweight and obese African-American and Caribbean children. A retrospective chart review was completed for 230 children. Receiver operating characteristic curves were generated to find the predictive performances of different tests against the OGTT. A1C alone is a poor discriminator of prediabetes in our study population, with low sensitivity (70%) and specificity (48.8%). BMI z score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Studies using adult cutoff values suggested an underestimation of the prevalence of diabetes and prediabetes [37,39]. Recently, Khokhar et al [40] found that HbA1c alone is a poor differentiator of prediabetes in a group of obese Caribbean and African-American children. Hence, it remains unclear if HbA1C and the same cutoff value should be used in children [3,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using adult cutoff values suggested an underestimation of the prevalence of diabetes and prediabetes [37,39]. Recently, Khokhar et al [40] found that HbA1c alone is a poor differentiator of prediabetes in a group of obese Caribbean and African-American children. Hence, it remains unclear if HbA1C and the same cutoff value should be used in children [3,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pre-diabetes is a necessary stage for diabetic patients. The early diagnosis of diabetes is an important way to reduce morbidity, complications, and mortality, and has important significance for the clinical evaluation and prevention of diabetes (Cefalu et al, 2014;Yi et al, 2014;Huang et al, 2016;Khokhar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Khokhar et al [25] studied predominantly African American and Caribbean youth (n=230) and found that HbA1 c had a receiver operating curve of 0.64 (95% CI, 0.56–0.72), showing that HbA1 c had poor sensitivity for detecting prediabetes when compared to OGTT. While 56% of the cohort had an elevated HbA1 c , 26% had an abnormal OGTT result, with 18% testing positive for both HbA1 c and OGTT.…”
Section: How Do These Tests Do When Compared To Each Other?mentioning
confidence: 99%